Modeling metal bioaccumulation and tissue distribution in killifish (Fundulus heteroclitus) in three contaminated estuaries. (5th November 2013) - Dutton, Jessica; Fisher, Nicholas S.
Abstract The present study experimentally assessed the uptake, loss, and resulting tissue distribution of As(V), Cd, Cr(III), Hg(II), and methylmercury (MeHg) in killifish (Fundulus heteroclitus) following aqueous exposure in water collected from 3 contaminated field sites—Baltimore Harbor and Elizabeth River (Chesapeake Bay), and Mare Island (San Francisco Bay)—using a radiotracer technique. Uptake rate constants (L g−1 d−1) were highest for MeHg (0.370–0.781) and lowest for As (0.00028–0.00065). Loss rate constants (d−1) were highest for As (0.046–0.096) and lowest for MeHg (0.006–0.009). Tissue distribution data showed that MeHg was redistributed around the body throughout the 9‐d depuration period, and drinking may be an uptake mechanism for Cd from the aqueous phase in higher‐salinity water. The kinetic parameters calculated in the present study were entered into a bioaccumulation model to calculate the predicted body burden of each metal at steady state and the percentage body burden attributable to dietary exposure on a site‐specific basis. Calculated body burdens varied between field sites for all metals except Cr. The predicted values for Cd, Hg(II), and MeHg matched independent field data from contaminated estuaries, indicating that the model can account for the major processes governing metal concentration in killifish. The diet accounted for >97% of the body burden of Cd and MeHg and was the predominant exposure route for As and Cr. Environ Toxicol Chem 2014;33:89–101. © 2013 SETAC